Pests Control and Acarology 2020
DOI: 10.5772/intechopen.81828
|View full text |Cite
|
Sign up to set email alerts
|

Trap Barrier System (TBS) as a New Tool for Rodent Pest Management in Irrigated Rice in Africa

Abstract: Rodent infestation poses a serious threat to smallholder farmers in both developed and developing countries where a large proportion of potential crop yield is lost. In Tanzania, the average annual yield loss of rice is estimated to be around 5-12%. Management of rodent pests in Africa relies mostly on the use of rodenticides which, however, are often applied only when damage has already occurred rather than routinely. Rodenticides used in this way are rarely economically and ecologically sustainable for manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This research supports the need for a LTBS to be managed at a community level and applied in strategic locations at key times to intercept rodents during a period of high dispersal. 56 Alternatively, a modification of the LTBS, the Community Trap Barrier System (CTBS) has been shown to be even more effective to reduce rodent numbers and crop damage in irrigated rice fields both in Asia 13 and Africa 57 . A CTBS involves the establishment of a lure rice crop 2-3 weeks ahead of the surrounding irrigated rice field, and is enclosed by a 20-50 sq m TBS with multiple-capture traps flushed with the TBS, and opening to the holes in the fence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research supports the need for a LTBS to be managed at a community level and applied in strategic locations at key times to intercept rodents during a period of high dispersal. 56 Alternatively, a modification of the LTBS, the Community Trap Barrier System (CTBS) has been shown to be even more effective to reduce rodent numbers and crop damage in irrigated rice fields both in Asia 13 and Africa 57 . A CTBS involves the establishment of a lure rice crop 2-3 weeks ahead of the surrounding irrigated rice field, and is enclosed by a 20-50 sq m TBS with multiple-capture traps flushed with the TBS, and opening to the holes in the fence.…”
Section: Discussionmentioning
confidence: 99%
“…56 Alternatively, a modification of the LTBS, the Community Trap Barrier System (CTBS) has been shown to be even more effective to reduce rodent numbers and crop damage in irrigated rice fields both in Asia 13 and Africa. 57 A CTBS involves the establishment of a lure rice crop 2-3 weeks ahead of the surrounding irrigated rice field, and is enclosed by a 20-50 sq m TBS with multiple-capture traps flushed with the TBS, and opening to the holes in the fence. A water-filled moat surrounds the TBS, and elevated soil mounds serve as walkways, leading to the opening to the MCTs in the TBS.…”
Section: Discussionmentioning
confidence: 99%
“…Field studies in rice cropping systems in Southeast Asia have shown that this method reduces the abundance of rodents over a large area surrounding the "trap crop" [39,40]. It has been shown in Tanzania that a 20m x 20m cTBS significantly reduces rodent abundance over an B D area of up to 16 ha of irrigated rice fields, leading to an increase in rice yield by 41% [41]. A simplified variant of cTBS, known as LTBS (Linear Trap Barrier System), has been tested in Asia [40,42] and a pilot study is currently being conducted in the delta of river Senegal.…”
Section: Figure 2 Examples Of Fences In Cultivated Plots From the Val...mentioning
confidence: 99%
“…This development of greater adoption of EBRM of rodent pests in China and in non‐rice crops is indeed a positive development. Moreover, the TBS has been successfully adopted as a tool for EBRM in rice crops in Eastern Africa 75 . Although the geographic spread of EBRM over the past decade is impressive, and impacts at a local scale have been reported, 34,35,54 quantitative data on the number of farmers who have adopted EBRM and the area of coverage at a district, region or provincial level is limited.…”
Section: Rice and Rodents – An Important Food Security Issue In Asiamentioning
confidence: 99%